2014
DOI: 10.1159/000358582
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fatty Acid-Binding Protein in Neonates with Imminent Necrotizing Enterocolitis

Abstract: Background: Intestinal fatty acid-binding protein (I-FABP) is a promising marker for necrotizing enterocolitis (NEC). It can be measured in plasma (I-FABPp) and urine (I-FABPu). Data on the best way to measure I-FABP (in plasma or urine) and the necessity of simultaneous measurement of the urinary creatinine concentration to correct for physiological variations in urine concentration are not available. This holds also true for the reciprocal relation between I-FABPp, I-FABPu and other more conventional laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…Conversely, L-FABP was shown to reflect organ hypoperfusion, including that in the kidney and liver4344. In neonates with necrotising enterocolitis, urinary L-FABP levels were shown to correlate with blood lactate levels45. The results of our principal component analysis were supported by these studies: Urinary NGAL correlated with markers of inflammation, whereas L-FABP showed significant linear correlations with hypoperfusion and hepatic injury markers (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Conversely, L-FABP was shown to reflect organ hypoperfusion, including that in the kidney and liver4344. In neonates with necrotising enterocolitis, urinary L-FABP levels were shown to correlate with blood lactate levels45. The results of our principal component analysis were supported by these studies: Urinary NGAL correlated with markers of inflammation, whereas L-FABP showed significant linear correlations with hypoperfusion and hepatic injury markers (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Some investigators have reported elevation of serum I-FABP levels in patients with occlusion of the superior mesenteric artery [6], strangulated obstruction of the bowel [7], celiac disease [8], necrotizing enterocolitis [9], and ulcerative colitis [10]. These findings suggest that I-FABP values can provide information regarding the extent of intestinal epithelial cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclical changes of hypoxemia with reoxygenation could represent an important mechanism for the presence of intestinal damage in OSA, independent of metabolic disturbances. Disruption of the gut wall integrity and leakage of macromolecules and microbial products from the intestinal lumen into the circulation can induce local and systemic inflammatory responses [19][20][21]. The present results suggest that OSA might contribute to gut mucosal injury, which might have important clinical implications.…”
Section: Discussionmentioning
confidence: 69%